Electric Vehicle Battery Thermal Management Using Hybrid Heat Pipe-Cold Plate Cooling System - Maalej Samah; Saad Imène; Hamdani Aya; Cherif Reyhan; Msaddek Rania; Zaghdoudi Mohamed Chaker (EPJ Web of Conferences)
This work deals with the thermal performance of a battery thermal management system in an electric vehicle composed of a heat pipe and cold plate. The experimental results demonstrate that the cooling system composed of a unique heat pipe and cold plate can disipate heat input power as high as 40 W with temperatures lower than the safety temperature of 60 °C. The heat transfer is analyzed using CFD simulations and IR measurements. It is demonstrated that the battery module's maximum temperature is well predicted by simulations, and IR temperature measurements are in good agreement with the simulated ones.